2018
DOI: 10.1089/sur.2018.110
|View full text |Cite
|
Sign up to set email alerts
|

A Propensity Score Analysis of Clostridium difficile Infection among Adult Trauma Patients

Abstract: Among trauma patients admitted >48 hours CDI occurred at a rate of 0.6%, much lower than anticipated. Patients in whom CDI developed had a significantly longer hospital LOS however, had no significant difference in odds of mortality or ICU LOS compared to patients without CDI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Of the 34 775 articles identified (Figure), 119 were full-text articles, and 86 (72.3%) of those articles met the selection criteria and were included in the systematic literature review . Among these, 66 articles evaluated incidence, and 20 articles evaluated LOS .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the 34 775 articles identified (Figure), 119 were full-text articles, and 86 (72.3%) of those articles met the selection criteria and were included in the systematic literature review . Among these, 66 articles evaluated incidence, and 20 articles evaluated LOS .…”
Section: Resultsmentioning
confidence: 99%
“…Of the 34 775 articles identified (Figure), 119 were full-text articles, and 86 (72.3%) of those articles met the selection criteria and were included in the systematic literature review . Among these, 66 articles evaluated incidence, and 20 articles evaluated LOS . One-fifth of the studies that assessed LOS (4 studies) scored 18 or more points of the 28 points possible on the Downs and Black scale and, thus, were considered to be of higher quality.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…10 Meanwhile several studies have shown higher in-hospital mortality rate, postoperative complications, prolonged hospitalizations, and hospital cost among surgical patients who develop CDI. 3,11,12 However, there has not been such a study investigating CDI rate and outcomes among common laparoscopic abdominal surgeries.…”
Section: Introductionmentioning
confidence: 99%